Meningkatkan Hasil Belajar Siswa pada Materi Sifat Keperiodikan Unsur Melalui Discovery Learning - Joni Suso Appulembang (Gema Pendidikan, 2021)
This study aims to determine the improvement of student learning outcomes through online discovery learning models. This research is a Classroom Action Research which is conducted in three cycles, each cycle consisting of 4 stages, namely: planning, action, observation, and reflection. The research subjects were 11 students of SMA Negeri 4 Gorontalo Utara, amounting to 11 people. The data sources came from teachers and students. Data collection techniques are by means of tests and non-tests. Data analysis used quantitative descriptive analysis techniques. The results showed an increase in student learning outcomes in the first cycle of 54.5% an average of 62.27; cycle II 81.8% an average of 71.8 and cycle III 81.8% an average of 73.63. The aspect of student activity in the I-II cycle is 70.5%; 82.5%; and 87.5% while the teacher in cycle I-III was 77.0%; 87.5%; and 93.75%. Based on the results of the study, it can be concluded that the application of the discoveri learning (discovery) learning model can improve student learning outcomes on the material periodic properties of elements, elemental stability and ionic bonds. Therefore, it is suggested that teachers in teaching subject matter should prioritize the use of the Discovery Learning (discovery) learning model.